Dasyatis hypostigma, Groovebelly Stingray - Pollom, R. (2020)
The Groovebelly Stingray (Dasyatis hypostigma) is a medium-sized (to 58 cm disc width) ray that occurs in the Southwest Atlantic from Espírito Santo, Brazil to southern Buenos Aires Province, Argentina. It inhabits estuaries and the inner continental shelf at depths of 5–80 m. This stingray is highly valued and the meat is sold locally. It is captured in intense and largely unmanaged artisanal and commercial demersal trawl and gillnet fisheries that operate throughout its geographic range. This species is also likely to be affected by coastal habitat degradation and conversion around large cities. In Buenos Aires Province, it declined in research trawl landings by more than 86% between 1981 and 2006, equivalent to a population reduction of >88% over three generations. Fisheries are intense in the Brazilian portion of its range and similar reductions are suspected there. The level of management in place in the ArgentinaUruguay Common Fishing Zone may have prevented such a steep trajectory there. Overall, due to the presence of intense and mostly unmanaged fishing pressure across its range, at least one decline in an index of abundance, and a decline in habitat quality, balanced with a suspected better situation in the Argentina-Uruguay Common Fishing Zone, it is suspected that the Groovebelly Stingray has undergone a population reduction of 50–79% over the past three generation lengths (27 years), and it is assessed as Endangered A2bcd.